Strategy to Fulfill the Requirements for Concession and Release of New Animal Breed or Strain - Bambang Setiadi (Indonesian Center for Animal Research and Development, 2016)
Law of the Republic of Indonesia Number 5 of 1994 on Ratification of the United Nations Convention on Biological Diversity and Regulation of the Minister of Agriculture of the Republic of Indonesia Number: 117/Permentan/SR.120/10/2014 regarding the concession and release of animal breed or strain in Indonesia should be followed up. This paper aims to improve the understanding of concession and release of animal breed or strain. Requirements of breed or strain concession has to declare (a) Its origin; (b) Original geographic distribution where the breed or strain formed; (c) Characteristics; (d) Genetic information; (e) The animal number and structure of their population; and (f) Animal picture. Requirements for the release of breed or strain should have (1) The method to obtain animal breed or strain; (2) Characteristics; (3) Genetic information; (4) New invention, unique, uniform and stable (NUUS); (5) The current number of animal; (6) Animal picture; (7) A guarantee certificate of quality standard; and (8) At the time of receipt of the request release, breed or strain has never been traded/distributed in Indonesia or already traded less than five years. Therefore, the government operational policy is necessary to regulate the preservation and improvement of animal genetic resources either breed or strain beneficial for future generations.